Pengaruh Penanganan Flebitis dengan Lidah Buaya terhadap Penurunan Flebitis di RS Intan Husada - Kurniawan Dewi Budiarti; Yiusep Subagja; Devi Ratnasari (STIKes Karsa Husada Garut, 2018)
Providing intravenous therapy for a long time can cause complications. One of the most common complications is phlebitis. Commonly in hospital phlebitis is treated by giving warm compresses and giving alcohol. Aloe vera therapy is not common to treat phlebitis. The general purpose of this study was to determine the effect of phlebitis handling techniques with aloe vera on the reduction of phlebitis in RSIH in 2018. The research method used was quasy experiment, purposive sampling was taken, the number of samples was 14 respondents, data collection was done by observation sheet.The results of the average phlebitis level before treatment with aloe vera were 1.82 and the mean phlebitis level after treatment with aloe vera 1.04 at RSIH in 2018. Conclusion there is the effect of phlebitis treatment with aloe vera on phlebitis reduction in RSIH in 2018. It is suggested that the results of this study indicate a decrease in phlebitis levels in patients who have phlebitis using aloe vera, therefore the use of aloe vera can be included in SOP for phlebitis.